Potato native and wound periderms are differently affected by down-regulation of FHT, a suberin feruloyl transferase. (March 2018) - Jin, Liqing; Cai, Qing; Huang, Wenlin; Dastmalchi, Keyvan; Rigau, Joan; Molinas, Marisa; Figueras, Mercè; Serra, Olga; Stark, Ruth E.
Abstract: Potato native and wound healing periderms contain an external multilayered phellem tissue (potato skin) consisting of dead cells whose cell walls are impregnated with suberin polymers. The phellem provides physical and chemical barriers to tuber dehydration, heat transfer, and pathogenic infection. Previous RNAi-mediated gene silencing studies in native periderm have demonstrated a role for a feruloyl transferase (FHT) in suberin biosynthesis and revealed how its down-regulation affects both chemical composition and physiology. To complement these prior analyses and to investigate the impact of FHT deficiency in wound periderms, a bottom-up methodology has been used to analyze soluble tissue extracts and solid polymers concurrently. Multivariate statistical analysis of LC-MS and GC-MS data, augmented by solid-state NMR and thioacidolysis, yields two types of new insights: the chemical compounds responsible for contrasting metabolic profiles of native and wound periderms, and the impact of FHT deficiency in each of these plant tissues. In the current report, we confirm a role for FHT in developing wound periderm and highlight its distinctive features as compared to the corresponding native potato periderm. Graphical abstract: Highlights: Soluble metabolite profiles of FHT-deficient and wild-type native periderms show significant differences. A metabolic rerouting to increase phenolic amines occurs in FHT-deficient native periderm. Differences between FHT-deficient and wild-type wound non-polar extracts are found only at Day 14. FHT-deficient native and wound periderms show an augmented hydrophilic-hydrophobic balance.